FAKTOR-FAKTOR YANG MEMPENGARUHI IMPULSE BUYING PADA CARREFOUR DI SURABAYA - GUNADHI, NOVY (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
This study aims to determine the effect of service quality on customer satisfaction, the effect of money available, shopping enjoyment , in store browsing , felt urge to buying of impulsively on impulse buying at Carrefour in Surabaya. The sampling technique used in this study is a purposive sampling. The respondent in this research is consumers who shop at Carrefour at least 4 times in a period of 3 months assuming not shopping just for everyday needs and aged at least 18 years old because consumer considered adult and can make decisions. The analysis technique in this study is Structural Equation Model (SEM) with software AMOS version 18. This study finds that money available have positive impact toward impulse buying, shopping enjoyment have positive impact toward in-store browsing, in-store browsing have positive impact toward felt urge to buy impulsively, felt urge to buy impulsively have positive impact toward impulse buying, shopping enjoyment have positive impact toward impulse buying at Carrefour in Surabaya.